Coenzyme Q10: Clinical Applications in Cardiovascular Diseases - Alma Martelli; Lara Testai; Alessandro Colletti; Arrigo F. G. Cicero (MDPI AG, 2020)
Coenzyme Q10 (CoQ10) is a ubiquitous factor present in cell membranes and mitochondria, both in its reduced (ubiquinol) and oxidized (ubiquinone) forms. Its levels are high in organs with high metabolism such as the heart, kidneys, and liver because it acts as an energy transfer molecule but could be reduced by aging, genetic factors, drugs (e.g., statins), cardiovascular (CV) diseases, degenerative muscle disorders, and neurodegenerative diseases. As CoQ10 is endowed with significant antioxidant and anti-inflammatory features, useful to prevent free radical-induced damage and inflammatory signaling pathway activation, its depletion results in exacerbation of inflammatory processes. Therefore, exogenous CoQ10 supplementation might be useful as an adjuvant in the treatment of cardiovascular diseases such as heart failure, atrial fibrillation, and myocardial infarction and in associated risk factors such as hypertension, insulin resistance, dyslipidemias, and obesity. This review aims to summarize the current evidences on the use of CoQ10 supplementation as a therapeutic approach in cardiovascular diseases through the analysis of its clinical impact on patients' health and quality of life. A substantial reduction of inflammatory and oxidative stress markers has been observed in several randomized clinical trials (RCTs) focused on several of the abovementioned diseases, even if more RCTs, involving a larger number of patients, will be necessary to strengthen these interesting findings.